Clinical and Epidemiological Overview of Influenza: A Literature Review - Rifki, Muhammad; Rachman, Amanda Azkiyah; Salsabila, Tsania Zulfa; Larasati, Anak Agung Ayu Regina; Paradiesta, Andi Frieskha Naurah (Jurnal Biologi Tropis, 2025)
Influenza is an acute contagious respiratory infection that remains a major global health concern due to its high transmissibility and ability to undergo genetic variations through antigenic drift and shift. This review aims to provide a comprehensive understanding of the definition, epidemiology, pathophysiology, clinical manifestations, diagnostic methods, management, complications, and preventive strategies of influenza based on recent scientific evidence. A narrative review method was employed by analyzing publications from 2008 to 2025, sourced from PubMed, ScienceDirect, and Google Scholar, using keywords such as “influenza,” “respiratory infection,” “antiviral therapy,” and “influenza vaccination.” The findings show that influenza affects approximately one billion people globally each year, with 3–5 million severe cases and 290,000–650,000 respiratory deaths, particularly among vulnerable groups including children, the elderly, pregnant women, and individuals with chronic diseases. The infection is caused by influenza viruses type A, B, C, and D, with type A being the most associated with epidemics and pandemics. Diagnosis is primarily based on clinical assessment supported by RT-PCR as the gold standard, while neuraminidase inhibitors such as oseltamivir and zanamivir remain the mainstay of therapy when administered early. Annual vaccination remains the most effective preventive measure, complemented by non-pharmacological interventions such as hand hygiene, mask use, and respiratory etiquette. In conclusion, strengthening surveillance systems, improving vaccination coverage, and enhancing early diagnostic capacity are essential strategies to reduce the global burden of influenza and its complications.